Perancangan Sistem Monitoring Aktivitas dan Posisi Ternak Menggunakan Platform Arduino dan Teknologi GPS - Hamid, Helson; Hasiri, Ery Muchyar; Mansyur, Ruslan (JURNAL INFORMATIKA, 2025)
Advancements in science and technology, particularly in computing and embedded systems, have encouraged the adoption of intelligent solutions in the livestock sector. Traditional grazing practices still present high risks, including livestock mortality, losses caused by broken restraints, and potential theft in areas that are not continuously supervised. To mitigate these issues, this study aims to design a livestock activity and location monitoring system based on NodeMCU and GPS modules, which can be monitored in real time through mobile devices. The research applies two primary approaches. An observational method was used to assess field conditions, identify user requirements, and evaluate the feasibility of technological implementation. A literature study was conducted to obtain theoretical foundations related to NodeMCU, accelerometers, and GPS-based monitoring systems. The system was tested using an accelerometer sensor capable of identifying three major activity conditions, namely idle (1.50 m/s²), walking (2.33 m/s²), and running (12.85 m/s²), thus providing representative indicators of livestock movement. Testing of the GPS module showed coordinate acquisition times ranging from 6 to 17 seconds, indicating stable data communication performance. In addition to activity and location tracking, the system integrates a geofencing feature that triggers an automatic alert when livestock cross predefined boundaries. These findings demonstrate that the developed system can enhance livestock security, reduce loss risks, and support the adoption of digital technology in livestock management.